Upregulation of cyclooxygenase-2 is associated with activation of the alternative nuclear factor kappa B signaling pathway in colonic adenocarcinoma - Shi, Guang (Am J Transl Res, 2015)
Cyclooxygenase-2 expression by malignant tumors, including colonic adenocarcinoma, is associated with increased tumor aggression and poor prognosis. Nuclear factor kappa B is a key regulator of cyclooxygenase-2 and is regulated by two pathways, the ‘canonical’ and the ‘alternative’ pathway. The alternative pathway is triggered by members of the tumor necrosis factor cytokine family, including RelB and p52. This present study was undertaken to evaluate cyclooxygenase-2 and the alternative nuclear factor-kappa B signaling pathway in colonic adenocarcinoma. Formalin-fixed, paraffin-embedded tissue samples diagnosed with colonic adenocarcinoma and a human colonic adenocarcinoma cell line, LS174, were studied. The expression of cyclooxygenase-2, RelB and p52 were determined using immunohistochemistry, immunofluorescence, and Western blots. Quantitative analysis of mRNA by real-time reverse transcriptase polymerase chain reaction and chromatin immunoprecipitation were performed on the tissue and cell samples. To investigate nuclear factor kappa B gene regulation of the cyclooxygenase-2 gene, dual luciferase assays were performed, and LS174 cells were transfected with RelB or p100/p52 short interfering RNA. Upregulation of cyclooxygenase-2 was associated with activation of the alternative nuclear factor kappa B signaling pathway components RelB, and p52, in colonic adenocarcinoma cells in tissues and the cell line, LS174. Chromatin immunoprecipitation assay determined that cyclooxygenase-2 gene was associated with both RelB and p52. A luciferase reporter assay showed that the nuclear factor kappa B enhancer of cyclooxygenase-2 was sufficient to regulate the transcriptional activity of a heterologous promoter in LS174 cells. RNA interference-mediated knockdown of RelB or p52 resulted in significant inhibition of cyclooxygenase-2 at both mRNA and protein levels in LS174 cells. These findings support a potential role for inhibition of components of the alternative nuclear factor kappa B signaling pathway, RelB-p52-cyclooxygenase-2, as a possible therapeutic target in the treatment of adenocarcinoma of the colon. Further studies on the role of this pathway in this and other malignancies are recommended.